2021
DOI: 10.3390/brainsci11070941
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione as a Molecular Marker of Functional Impairment in Patients with At-Risk Mental State: 7-Tesla 1H-MRS Study

Abstract: A substantial number of individuals with clinical high-risk (CHR) mental state do not transition to psychosis. However, regardless of future diagnostic trajectories, many of these individuals develop poor social and occupational functional outcomes. The levels of glutathione, a crucial cortical antioxidant, may track variations in functional outcomes in early psychosis and prodromal states. Thirteen clinical high-risk and 30 healthy control volunteers were recruited for a 7-Tesla magnetic resonance spectroscop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…We observed that in untreated first episode patients, an elevated ACC GSH at the time of presentation occurred in those with more florid disorganization [73] but most of these subjects responded briskly to the regular antipsychotic treatments over the next 6 months [69]. Help seeking subjects with subthreshold psychotic symptoms display better social and occupational functioning when ACC GSH levels are higher [77]. In the metaanalysis of Das and colleagues we noted a small but significant increase in ACC GSH in bipolar disorder, a phenotype that is often associated with better functional outcomes than schizophrenia [64].…”
Section: Intracortical Gsh In Schizophrenia: Mrs Studiesmentioning
confidence: 85%
See 1 more Smart Citation
“…We observed that in untreated first episode patients, an elevated ACC GSH at the time of presentation occurred in those with more florid disorganization [73] but most of these subjects responded briskly to the regular antipsychotic treatments over the next 6 months [69]. Help seeking subjects with subthreshold psychotic symptoms display better social and occupational functioning when ACC GSH levels are higher [77]. In the metaanalysis of Das and colleagues we noted a small but significant increase in ACC GSH in bipolar disorder, a phenotype that is often associated with better functional outcomes than schizophrenia [64].…”
Section: Intracortical Gsh In Schizophrenia: Mrs Studiesmentioning
confidence: 85%
“…Higher intracortical glutamate levels relate to reduced social function [69,125] and poorer treatment response [81] in early stages and reduced cortical grey matter [83,126,127]. On the other hand, higher GSH levels relate to faster treatment response [69], better functioning [77] and preserved cortical grey matter [102] [See [128,129] for association with peripheral GSH]. We recently observed opposing influence of glutamate and GSH on the intrinsic connectivity within the dACC node of the Salience Network in first episode psychosis [72].…”
Section: Glutathione -Glutamate Relationshipmentioning
confidence: 99%
“…MRS measurements were acquired using a Siemens MAGNETOM 7 T head-only MRI scanner (Siemens, Erlangen, Germany) and a site-built head coil (8-channel transmit, 32-channel receive) at the Centre for Functional and Metabolic Mapping of Western University (London, Ontario). This acquisition has been employed in our prior MRS studies 48 , 52 , 53 . Further details of the acquisition and spectral fitting are described in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…We observed that in untreated first episode patients, an elevated ACC GSH at the time of presentation occurred in those with more florid disorganization [ 73 ] but most of these subjects responded briskly to the regular antipsychotic treatments over the next 6 months [ 69 ]. Help seeking subjects with subthreshold psychotic symptoms display better social and occupational functioning when ACC GSH levels are higher [ 77 ]. In the meta-analysis of Das and colleagues we noted a small but significant increase in ACC GSH in bipolar disorder, a phenotype that is often associated with better functional outcomes than schizophrenia [ 64 ].…”
Section: Intracortical Gsh In Schizophrenia: Mrs Studiesmentioning
confidence: 99%
“…Higher intracortical glutamate levels relate to reduced social function [ 69 , 123 ] and poorer treatment response [ 81 ] in the early stages and reduced cortical grey matter [ 83 , 124 , 125 ]. On the other hand, higher GSH levels relate to faster treatment response [ 69 ], better functioning [ 77 ], and preserved cortical grey matter [ 101 ] (See also [ 126 , 127 ] for association with peripheral GSH). We recently observed an opposing influence of glutamate and GSH on the intrinsic connectivity within the dACC node of the Salience Network in first episode psychosis [ 72 ].…”
Section: Glutathione—glutamate Relationshipmentioning
confidence: 99%